Contrastación metodológica del PDOT cantonal y parroquial con el grado de interacción en el límite legal administrativo. caso Riobamba-Licán - Guijarro Paguay, Magda Lucinda (2025)
Territorial planning is a key instrument for guiding the orderly and sustainable growth of geographic spaces, especially in contexts where urban expansion and interaction between different jurisdictions generate complex challenges. Within this framework, the Development and Land-Use Plans (PDOT) of Riobamba and the rural parish of Licán, both located in the province of Chimborazo, serve as essential technical and regulatory references for steering territorial development and improving the quality of life of their inhabitants. However, the limited coordination between these instruments—particularly in border areas where conurbation occurs—reveals shortcomings in infrastructure, basic services, mobility, and population growth, highlighting weak physical integration and administrative coordination. This study aims to analyze and compare the methodologies used in the formulation of the PDOTs of both territories, with a focus on the diagnostic and policy design phases, evaluating their ability to address shared challenges. Based on a critical analysis, the study proposes alternatives to strengthen integrated planning, promoting more cohesive, equitable, and sustainable territories.